2013
DOI: 10.1016/j.tim.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the human skin microbiome

Abstract: An abundant and diverse collection of bacteria, fungi and viruses inhabit the human skin. These microorganisms have been reported to vary between individuals and between different sites on the skin. The factors responsible for the unique variability of the skin microbiome are only partially understood, but results suggest host genetic and environmental influences play a major role. Today, the steady accumulation of data describing the skin microbiome, combined with experiments designed to test the biological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
307
3
18

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(333 citation statements)
references
References 92 publications
(108 reference statements)
5
307
3
18
Order By: Relevance
“…S. aureus may also show enhanced adherence properties to skin cells, which has been shown when comparing atopic eczema sufferers with normal control subjects. 240,241 Other studies reviewed elsewhere 242,243 have suggested that the balance of pathogenic and synbiotic bacterial species on the skin is altered in atopic eczema, resulting in an agitated skin microbiome.…”
Section: Rationalementioning
confidence: 99%
“…S. aureus may also show enhanced adherence properties to skin cells, which has been shown when comparing atopic eczema sufferers with normal control subjects. 240,241 Other studies reviewed elsewhere 242,243 have suggested that the balance of pathogenic and synbiotic bacterial species on the skin is altered in atopic eczema, resulting in an agitated skin microbiome.…”
Section: Rationalementioning
confidence: 99%
“…Several reviews have described the role and impact of skin microbiome on disease 17, 18, 19, 20, 21, 22. However, to date, no structured review has been conducted to evaluate the feasibility, suitability and potential use of the skin microbiome as biomarker for early phase clinical drug development.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that skin microbiome changes in response to various stimuli such as food, drugs, age, gender, physiological status etc., implying changes of the AMP cocktail [178]. These changes can be examined by the sensitive quantitative proteomics techniques, which are well suited to monitor AMP levels at various sites of the body in different physiological or pathological conditions [179].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%